THE ROLE OF NAHDLATUL ULAMA IN CREATING AN R20 FORUM AS INDONESIA'S SOFT POWER IN THE WORLD - Sri Haryanto; Robingun Suyud El Syam (Jurnal Scientia, 2023)
The purpose of this research is to unravel the role of Nahdlatul Ulama in making the R20 Forum as Indonesia's Soft Power in the international arena, by helping to ensure that religion can function as a source of real and dynamic global solutions, not as a source of problems. This article uses a combination of qualitative and quantitative research methods. Research was carried out at the R20 Forum activities on 2-3 November 2022 in Nusa Dua, Bali. The research object focuses on Soft Power Indonesia in the international arena, with library data sources and descriptive analysis. The research concludes: that the R20 forum was initiated by Nahdlatul Ulama as an effort to promote mutual understanding, a culture of peace, and harmonious coexistence among diverse people in the world, religions, and nations, by ensuring the role of religion as a source of dynamic solutions, not as a problem. The agenda becomes Soft Power Indonesia in the international arena by presenting a model of religion, nation and state in harmony. In addition to aspects in the field of tourism, politics and the economy. Through this agenda, Nahdlatul Ulama has a strategic role to play in increasing Indonesia's position in the international arena. This study develops its setting and orientation by integrating religion as a solution to global problems in internal and multilateral problems. This shows the prominent role of Nahdlatul Ulama, because specific cases show a role in social community.